SISTEM PENDIDIKAN ISLAM DI ANDALUSIA: MODEL KEILMUAN DAN WARISAN INTELEKTUALNYA - Fajar Al Mahmudi; Feby Ayu Diwa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study analyzes the Islamic education system in Andalusia as a model of scholarship and intellectual heritage that played a significant role in the advancement of Islamic civilization and the Western world during the classical period. This study aims to explain the structure of the education system, the characteristics of the scientific model, and the intellectual contribution of Andalusia to the development of the global scientific tradition. The study uses a qualitative method with a historical descriptive approach through literature study that utilizes secondary data in the form of books, scientific articles, and historical sources. Then, descriptive analytical analysis is carried out to understand the dynamics of education within the socio political and cultural context. The research findings indicate that the Andalusian education system emerged from a socio-political transformation that fostered government stability, open access to knowledge, and integration between religious and rational knowledge through educational institutions such as mosques, universities, scholarly assemblies, and large libraries. The research findings confirm that the support of the rulers, an organized institutional structure, an integrative curriculum, and scientific traditions such as the rihlah and the ijaza system gave birth to multidisciplinary scholars and made Cordoba a center of world civilization. Furthermore, Andalusian education served as a bridge for the transfer of knowledge from the Islamic world to Europe through the translation of Arabic scientific works. The implications of the research indicate that the Andalusian integrative education model has conceptual relevance as a reference for the development of contemporary Islamic education that is inclusive, holistic, and oriented towards the development of knowledge.